2015
DOI: 10.5733/afin.056.0311
|View full text |Cite
|
Sign up to set email alerts
|

Docytochrome c oxidase 1Gene Sequences Differentiate Species of Spirostreptid Millipedes (Diplopoda: Spirostreptida: Spirostreptidae)?

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Although our relatively small taxon sampling, the phylogenetic analysis strongly recovers Sechelleptus as monophyletic and discriminates at least two or three different groups. Furthermore, the mean inter-specific distance values (14.9% for COI and 5.1% for 16S) were remarkably similar to previous studies that reported the presence of high genetic divergence among population of different spirostreptid species (Mwabvu et al 2013(Mwabvu et al , 2015, suggesting the existence of more than one species in those taxa. It is argued that high level of divergence between identified spirostreptid species may indicate that changes in genital morphology occur rather slowly relative to the high rate of substitution in mitochondrial sequences (especially for COI), and may underestimate species diversity.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although our relatively small taxon sampling, the phylogenetic analysis strongly recovers Sechelleptus as monophyletic and discriminates at least two or three different groups. Furthermore, the mean inter-specific distance values (14.9% for COI and 5.1% for 16S) were remarkably similar to previous studies that reported the presence of high genetic divergence among population of different spirostreptid species (Mwabvu et al 2013(Mwabvu et al , 2015, suggesting the existence of more than one species in those taxa. It is argued that high level of divergence between identified spirostreptid species may indicate that changes in genital morphology occur rather slowly relative to the high rate of substitution in mitochondrial sequences (especially for COI), and may underestimate species diversity.…”
Section: Discussionsupporting
confidence: 88%
“…The relationships among the outgroups were not the primary focus of the present study, but are consistent with previous studies (Mwabvu et al 2013(Mwabvu et al , 2015Tinago et al 2017) that showed paraphyletic groups suggesting the presence of cryptic species (i.e., Bicoxidens spp.) and possible identification errors in the GenBank database.…”
Section: Phylogenysupporting
confidence: 92%
See 1 more Smart Citation
“…Large COI sequence divergences are further observed in the genera Thyropygus Pocock, 1894 andAnurostreptus Attems, 1914 (Spirostreptida, Harpagophoridae) with intraspecific values of 0-12 and 0-6% (mean: 6 and 3%) respectively, and interspecific divergences of 5-18 and 9-11% (mean: 14 and 11%) respectively (Pimvichai et al 2014). In the family Spirostreptidae Brandt, 1833, the intergeneric COI sequence divergences are 6.83-26.81% (mean: 18.43%) (Mwabvu et al 2015). As such, the amounts of sequence differentiation among the four new Apeuthes species are approximately in line with species-level divergences in other spirostreptid and spirobolid genera.…”
Section: Dna Barcodementioning
confidence: 90%
“…The lowest COI sequence divergence is with Litostrophus (11-18%; mean: 15%). In the order Spirostreptida, family Spirostreptidae the intergeneric COI sequence divergences are 6.83-26.81% (mean: 18.43%) (Mwabvu et al 2015). Hence, taken together, the amount of COI sequence divergence between Coxobolellus, gen. nov. and other pseudospirobolellid, pachybolid and spirostreptid genera supports its recognition as a separate genus.…”
Section: Descriptionmentioning
confidence: 99%